Species and Economic Value of Peat Swamp Ichthyofauna for Community in Kapuas Kiri Hulu Village Sintang Regency - Syukur, Muhammad; Sumarni, Sri; Afriani, Rachmi; Nazarudin (Universitas Nusa Bangsa, 2025)
Ichthyofauna is a term for fish fauna or a group of fish. Peat swamp ichthyofauna refers to the entire collection of fish found in peat swamps. Studies on peat swamp ichthyofauna are important not only to identify their species but also to understand their economic roles for the local community. This study aims to identify the species and economic value of peat swamp ichthyofauna for the community in Kelurahan Kapuas Kiri Hulu, Sintang Regency. The research utilized interview and observation methods. Interviews were conducted with local residents to gather information regarding the species and economic value of peat swamp ichthyofauna. Observations were carried out to determine observation points. Ichthyofauna data collection was conducted at six observation points selected to represent the characteristics of the research area. The first observation point was in a community oil palm plantation area, the second in a natural peat swamp without human activity, and the third, fourth, and fifth points in small rivers with different characteristics connecting the Kapuas River in West Kalimantan to the peat swamp area. The sixth observation point was a peat swamp area utilized for community activities. The results of the study identified 14 species of peat swamp ichthyofauna in Kelurahan Kapuas Kiri Hulu, Sintang Regency, including Sepat Mutiara (Tricogaster leeri), Sepat Rawa (Tricogaster tricoptherus), Sepat Siam (Tricogaster pectoralis), Beto (Anabas testudineus), Delak (Channa striata), Seluang Bujur (Rasbora argyrotaenia), Engkarit (Puntius lineatus), Biawan (Helestoma temanncki), Senara (Parambassis ranga), Landin (Macrones gulio), Lele Rawa (Clarias teijsmanni), Selomang (Betta foreman), Patik (Mystus namurus) dan Rik (Mystus micracantus)). Peat swamp ichthyofauna holds economic value for the local community, both as fresh fish for sale and as processed products such as fermented fish (pekasam), smoked fish (salai), salted fish, wet crackers, and ornamental fish.